Ultrasonic pretreatment on Alcalase or goat milk casein: impact on protein hydrolysis kinetics and on solubility and in vitro antioxidant activity of hydrolysates - Guimarães, Alécia Daila Barros (2022)
Goat milk is a highly nutritious food, easy to digest and absorb, which has been attracting the interest of the population, researchers and industries. Caseins are the main proteins in goat milk and have lower allergenicity compared to bovine casein. Goat milk has great potential for the generation of new products, such as protein hydrolysates and bioactive peptides with techno- functional properties and potentially biological. Enzymatic hydrolysis is one of the main methods for obtaining protein hydrolysates, however it has limitations such as the long hydrolysis time, low yield, and high cost. Previous studies have suggested the use of ultrasound (US) to improve enzyme performance. Thus, this study evaluated the effect of ultrasound (US) in the pretreatment of Alcalase and goat milk casein (GMC) to improve the hydrolysis performed at 25, 40 or 60 °C for up to 180 min. Evaluation was based on reaction rate, degree of hydrolysis (DH), TCA-soluble protein concentration, solubility and in vitro antioxidant activity. US pretreatment on Alcalase (40°C/60 min) or on GMC (60°C/30 min) increased the relative enzyme activity by up to 15.6 and 18.1%, respectively. Thus, US promoted an increase in the solubility (up to 37% at pH 4.0) and in vitro antioxidant activity (up to 37% for the ABTS assay) of the hydrolysates after 180 min of reaction. Therefore, the results found expand the use of ultrasound, demonstrating that this technology can be used both on Alcalase and on GMC to enhance the hydrolysis, aiming to obtain hydrolysates and bioactive peptides with better nutritional and techno-functional appeal. Keywords: Ultrasound. Goat milk. Peptides. Protein Solubility. Techno-functional properties. Biological Properties.